Urgensi Penggunaan Smart Contract dalam Transaksi Jual Beli di E-Commerce - Laila Alfina Mayasari Rizqi; Dedi Farera Prasetya (CV Rewang Rencang, 2022)
The increasingly massive use of the internet is now affecting the world economy marked by the birth of E-Commerce. This E-Commerce mechanism that does not bring together sellers and buyers directly raises various problems over the subjective and objective terms of the sale and purchase agreement. Therefore, the article aims to analyze the urgency of using the concept of Smart Contract technology-based agreements in the sale and purchase transactions in E-Commerce. The result obtained is the use of Smart Contracts in the sale and purchase transactions in E-Commerce is considered very important to see the advantages in terms of security, verification, changes in the content of the agreement, and the strength of evidence.